Prescribing pattern and utilization of selected antimicrobials in a tertiary hospital of Nepal - Acharya, Upasana; Mahat, Ravi; Acharya, Subhash Prasad; Pahari, Bishnu; Tripathi, Prashant (Grande Medical Journal, 2019)
Introduction: This study was done to understand the purpose of using higher grade antimicrobials in a one year period and to compare the consumption of commonly prescribed parenteral antimicrobial agents in four consecutive years in a tertiary care hospital of Nepal. Materials & Methods: A retrospective observational study was carried out to collect the information on prescription of selected six classes of antimicrobial for all admitted patients aged 2 years or above for a one-year period. Further, the antimicrobial consumption tool 2016 was used to calculate defined daily dose (DDD) per 100 bed days of commonly dispensed parenteral antimicrobials for four consecutive years. Results: A total of 2568 antimicrobial supply forms prescribing higher grades antimicrobials were analyzed. The indications for use of antimicrobials were mainly for empiric treatment. Among the infections being treated, lower respiratory tract infection (LRTI) was the most frequent cause. Piperacillin-tazobactam was most frequently prescribed followed by Meropenem. Also, DDD for commonly used parenteral antimicrobials showed increasing trends over four consecutive years. Conclusion: The prescription of higher grades of antimicrobial for empiric treatment and surgical prophylaxis need to be monitored. The rate of consumption of such antimicrobials could not be assessed due to lack of similar studies but the increase in DDD/100 bed days each year suggested the rise in consumption of antimicrobial in the same institution.